GREEN FAÇADES - El-Zoklah, Marwa Salem (MATTER: International Journal of Science and Technology, 2016)
The Green Areas and Sustainable Architecture are very important to the ECO-System and the people live around them. However much of them has been degraded according to human behavior among the environment. There are many phases to reach sustainability; first to stop abuse and think green, second change the idea of construction buildings to green buildings, third reusing and recycling, finally monitoring and maintenance. The main aim of the paper develops is how to compensate the lake of green spaces by using green façades technology. Green Façade refers to how you can built with reduction of damaging environment, maximize the indoor air quality, saving energy and integrating natural vegetation with building construction. The importance of green façade is how to maximize indoor and outdoor quality and compensate the lake of green spaces. Methodology includes literature review and analytical examples. Research is expected to conclude some recommendations to use green façades technology and knowing the impact of using it.